Recommended Personal Protective Equipment for Cochlear Implant and Other Mastoid Surgery During the COVID‐19 Era. (15th August 2020) - Lawrence, Rachael J.; O'Donoghue, Gerard; Kitterick, Pádraig; O'Donoghue, Kevin; Hague, Richard; Mitchell, Laura; Lycett‐Ranson, Zoe; Hartley, Douglas E.H.
Abstract : Objectives/Hypothesis: The overall aim of this study was to evaluate personal protective equipment (PPE) that may facilitate the safe recommencement of cochlear implantation in the COVID‐19 era, with the broader goal of minimizing the period of auditory deprivation in prelingually deaf children and reducing the risk of cochlear ossification in individuals following meningitis. Methods: The study design comprised 1) an objective assessment of mastoid drilling‐induced droplet spread conducted during simulated cochlear implant (CI) surgery and its mitigation via the use of a protective drape tent and 2) an evaluation of three PPE configurations by otologists while performing mastoid drilling on ex vivo temporal bones. The various PPE solutions were assessed in terms of their impact on communication, vital physiological parameters, visual acuity and fields, and acceptability to surgeons using a systematic risk‐based approach. Results: Droplet spread during simulated CI surgery extended over 2 m, a distance greater than previously reported. A drape tent significantly reduced droplet spread. The ensemble of a half‐face mask and safety spoggles (foam lined safety goggles) had consistently superior performance across all aspects of clinical usability. All other PPE options were found to substantially restrict the visual field, making them unsafe for microsurgery. Conclusions: The results of this preclinical study indicate that the most viable solution to enable the safe conduct of CI and other mastoid surgery is a combination of a filtering facepiece (FFP3) mask or half‐face respirator with safety spoggles as PPE. Prescription spoggles are an option for surgeons who need to wear corrective glasses to operate. A drape tent reduces droplet spread. A multicenter clinical trial to evaluate the effectiveness of PPE should be the next step toward safely performing CI surgery during the COVID‐19 era. Level of Evidence: 4 Laryngoscope, 130:2693–2699, 2020